Association between corporate governance and related party transactions: a case study of banking sector of Bangladesh - Sharkar, Mohammad Zakir Hossain; Sobhan, Md. Abdus; Sultana, Shahida (BRAC University, 2010)
This paper critically examines the relationship between corporate governance and related party transactions (RPTs). RPTs have become a global hot topic due to the link between undisclosed RPTs and the collapse of some high profile companies. This paper analyses the current literature and establishes a relationship between corporate governance indicators and the number of RPTs by using Bangladesh banking sector data.